Local Leaders’ Perceptions about Sustainable Tourism Development in Timor-Leste - Vong, Manuel; Silva, João Albino; Pinto, Patrícia (Journal of Tourism, Sustainability and Well-being, 2015)
Timor-Leste is a small island that emerged as Asia’s newest nation in 2002, and it is largely unknown as a tourism destination in the world, with geographic, natural, and socio cultural weaknesses and vulnerability. In this country, tourism is considered as one of the priorities for the national economic development, in addition to agriculture, and petroleum. However, in a new destination, which is also in the first stage of tourism development, the involvement of stakeholders is very limited both on the supply and the demand sides. This situation presents a major challenge to the achievement of a sustainable tourism development. Moreover, the study of tourism in this country is a very recent phenomenon. In this context, the objective of this study is twofold. Firstly, it intends to examine the perceptions of the local leaders (from the public sector, the private sectors and from non-governmental organizations) regarding the sustainable tourism development concept; and secondly, to understand to what extent these leaders take initiatives in voluntary actions towards sustainable tourism development at the local level, as well as their motivations and difficulties in this process.